Perilaku Orangtua Yang Merokok Terhadap Kesehatan Anak (0-5 Tahun) - Ramdani, Hasbi Taobah; Wahyudin, Wahyudin; Nursela, Annisa Alail (Jurnal Keperawatan 'Aisyiyah, 2018)
Many smokers are aware of the consequences of smoking, but still smoking and difficult to eliminating the habit. Many people who smoke in the home without caring for members of the family, let alone toddlers who become passive smokers. Release, the child is very easy by way of the air, and susceptible to various diseases caused. The purpose of this study is to find out more about the behavior of parents who smoke on the children’s health (0-5 years) in District Bungbulang. The researchers chose to use a qualitative research design with a phenomenological approach. Data completion technique in this research. There were 3 informants who participated in this research, taken using the snowball sampling technique. The results of this study obtained four themes of knowledge about cigarette, reactions to stop smoking at home, smoking habit, and children health. Racial informants are unaware of the dangers of smoking and its effects on children who become passive smokers. However, because of the lack of knowledge about health and knowledge about the impact of smoking on the health of passive smokers, especially children who are insuring. Smokers Find alternatives to embellish the desire, such as doing activities that also avoid the main reasons that cause the desire to smoke. Should use a cigarette replacement, such as candy and multiply the consumption of milk, fruits and vegetables.